PENGARUH KURS, GROSS DOMESTIC PRODUCT DAN SOLVABILITAS TERHADAP RETURN SAHAM INVESTOR PADA PERUSAHAAN PERTAMBANGAN - Dewi, Martina Carissa; Artini, Luh Gede Sri (E-Jurnal Manajemen; Vol 8 No 10 (2019), 2019)
The level of return obtained by investors is influenced by microeconomic and macroeconomic factors. This study aims to obtain empirical evidence regarding the effect of exchange rates, Gross Domestic Product and solvency on stock returns. This research was conducted at the mining company in the coal sub-sector on the Indonesia Stock Exchange. All the coal mining sub-sector companies listed on the Stock Exchange for the period 2014-2017 used as the population. The method of determining the sample used is using a saturated sampling technique. Multiple linear regression test used as the data analysis on this research. Based on the results of the analysis of this study it was found that the exchange rate and GDP had a negative and significant effect on stock returns. The solvency proxied by DER has a positive and significant effect on stock returns. Keywords: Exchange Rate, Gross Domestic Product, Solvability and Return.